Gagasan Penerapan Undang-Undang Nomor 31 Tahun 1999 Juncto Undang-Undang Nomor 20 Tahun 2001 Tentang Pemberantasan Tindak Pidana Korupsi Dalam Penegakan Hukum Terhadap Korporasi Pembakar Hutan Dan Lahan Di Indonesia - Sihombing, Mual Ady Putra; Effendi, Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Forest and land fires that occur almost every year cause losses to the people of Indonesia rangingfrom health, social, ecological, economic and also disruption, the world bank (world bank) revealed thetotal loss of Indonesia the impact of forest and land fires during 2019 reached US 5.2 billion or equivalentto Rp. 72.95 trillion. The impact of forest and land fires is large, so law enforcement must be effective.Difficulties in law enforcement in the criminal environment which generally causes frequent failure of casesin court are regarding the presentation of evidence (proof) and the determination of the causal relationshipbetween the act and the consequences of the act (cause and effect). forest and land fires carried out bycorporations can be held accountable for using the Corruption Act to protect the interests of the state interms of returning state financial losses incurred due to forest and land fires. If using a law onenvironmental protection and management that protects the sustainable use of forests and land. So it isnecessary to carry out the idea of applying Law Number 31 of 1999 Juncto Act Number 20 of 2001concerning eradicating criminal acts of corruption against corporate forest and land burners in Indonesia.This type of research is a normative legal research that is research conducted with a literature studyor literature study in finding data. This research is descriptive in nature which provides detailed anddetailed data on existing problems. In this paper using qualitative data analysis which means to explain andconclude about the data that has been collected by the author. This research uses secondary data orscientific data that has been codified.The results of this study are to explain that the application of environmental protection andmanagement laws is not optimal in law enforcement against criminal prosecution of forest and land burnersso that it is difficult to be held accountable, because forest and land fires have an impact on the country'sfinances or economy and environmental laws are very it is difficult to prove environmental crimescommitted by corporations so that there are often stopping investigation letters (SP3) against forest andland-burning corporations in Indonesia which causes law enforcement to be unimportant. Thus, cases offorest and land fires carried out by corporations can ensnare corporations and hold corporationsresponsible for forest and land burners. Article 2 of Law Number 31 of 1999 Juncto of Law Number 20 of2001 Concerning Eradication of Corruption. With the application of the Anti-Corruption Law, lawenforcement can work effectively and corporations can be held accountable and provide a deterrent effectfor forest and land-burning corporations. The idea or idea that the author offers for the law in the future isto be appled.Keyworlds : Implementation – Corporate – Coruuption.